Baseline Survey on Multilingual and Transdisciplinary Urban Arts Education - Kovačič, Mojca; Ličen, Daša; Pisk, Marjeta; Tomazin, Andrej (ZRC SAZU, Založba ZRC, 2021)
The baseline survey on multilingual and transdisciplinary urban arts education is the result of the first part of the UrbArt project, which supports low-skilled adults in marginalized communities with urban arts activities and educational approaches. The aim of the baseline survey was to identify national and transnational needs and challenges related to marginalization in culture and education, as well as performance indicators for urban arts education, taking into account the concepts of transdisciplinarity and multilingualism. Five partner countries from Austria, Iceland, Portugal, Slovenia and the United Kingdom participated in the study. The survey involved people working as education providers or arts workshops in the areas covered by the project and asked them to share their experiences, describe their needs and challenges, and identify problems they face in their work with deprivileged or marginalized people or communities. Questionnaires, interviews and focus groups based on the same starting points formed the methodological basis. The publication presents the processes and outcomes of the work, concludes with key findings at European level and makes recommendations for the potential of social access and empowerment of deprivileged and marginalized adult individuals and communities through urban arts education.